Seasonal Variation of Calving in Murrah Buffalo in Bihar - Potdar, V.V.; Khadse, J.R.; Joshi, S.A.; Gaundare, Y.S.; Phadke, N.L.; Swaminathan, M.; Pande, A.B. (Journal of Buffalo Science, 2019)
The present study was carried out to estimate the seasonal variation of calving in Murrah buffaloes. The study was conducted in North West alluvial plain of Bihar (Chappra, Siwan and Samastipur), of India on 773 Murrah buffaloes, and these buffaloes were inseminated during June 2010 to December 2014 at BAIF’s field Artificial Insemination centres which provide door-step artificial insemination service at village’s level. The result indicated that the calving of Murrah buffaloes occurred throughout the year. In Chhapra maximum calving observed in August, i.e. 17% while 14% in October. September and November 13% each. Based on season majority of calving observed between July to January. In Samastipur maximum calving observed in August 16% while in September 14 % followed by November 13% and October month 11%. Based on season majority of calving observed between July to January months. In Samastipur maximum calving observed in August 16% while in September 14% followed by November 13% and October 11%. Based on season majority of calving found between July to January months. It could be concluded that Murrah buffaloes tend to calve more in the days with shorter photoperiod as compared to days with more extended photoperiod.